Proceedings of the Fourth International Conference on Learning Analytics and Knowledge 2014
DOI: 10.1145/2567574.2567590
|View full text |Cite
|
Sign up to set email alerts
|

Analytics of the effects of video use and instruction to support reflective learning

Abstract: Although video annotation software is no longer considered as a new innovation, its application in promoting student self-regulated learning and reflection skills has only begun to emerge in the research literature. Advances in text and video analytics provide the capability of investigating students' use of the tool and the psychometrics and linguistic processes evident in their written annotations. This paper reports on a study exploring students' use of a video annotation tool when two different instruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
2
28
1
Order By: Relevance
“…These findings suggest that the instructional design needs to offer some further guidance to the students on how to use the new tool effectively and provide a clear rationale outlining the value that such tool use can play in facilitating student learning and therefore, future academic performance. In a recent study, Gašević et al [10] demonstrated that by altering the external conditions (i.e. graded versus nongraded) had a significant impact on the quality and quantity of video annotations made in a course.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the instructional design needs to offer some further guidance to the students on how to use the new tool effectively and provide a clear rationale outlining the value that such tool use can play in facilitating student learning and therefore, future academic performance. In a recent study, Gašević et al [10] demonstrated that by altering the external conditions (i.e. graded versus nongraded) had a significant impact on the quality and quantity of video annotations made in a course.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have used learning analytics and data-mining to investigate students' actual engagement with lecture videos by clustering students based on video tool access [4] and how such objective data when coupled with results on related quizzes [20] can inform instructors' pedagogical approaches and intervention strategies. Similarly, related studies into students' annotations have used logged data to investigate the length of time-stamped annotations compared to hand-written notes [21] and patterns in the linguistic and cognitive processes inherent in the text of the annotations [10]. Although there are numerous studies reporting associations between grades and variables obtained from data traces (for example [24]), there is a lack of analysis to expand these associations in order to unpack students' approaches to learning to understand the underlying associations.…”
Section: Related Workmentioning
confidence: 99%
“…However, the data used for the study was largely based on self-reported information collected via pre and post surveys and interviews, albeit also included direct observations of student and teacher interactions with MAT. Recent studies (Gašević, Mirriahi, & Dawson, 2014;Pardo et al, 2015) have used video analytics techniques to analyse detailed event streams and investigate how first-year university students use and engage with video annotation tools.…”
Section: Engagement With Course Videosmentioning
confidence: 99%
“…Moreover, findings suggest that the benefits from optional forum assignments are very low whereas compulsory forum assignments might be related to higher performance [15]. In addition, the work in [16] made an in-depth analysis of the use of video annotation, which can be seen as an optional activity for students.…”
Section: Related Workmentioning
confidence: 99%